Appeals to the judicial committee of the privy council / Rashidah Abu Bakar - Abu Bakar, Rashidah (Faculty of Law, 1978)
In this exercise, the writer in Chapter I deals mainly with the historical aspect of appeals to the Judicial Committee and a summary of the natvire of work carried out. The writer also devotes some time to a discussion of the historical and practical similarities and differences between the House of Lords and the Judicial Committee«